2018
DOI: 10.1182/bloodadvances.2018020628
|View full text |Cite
|
Sign up to set email alerts
|

Impact of somatic and germline mutations on the outcome of systemic mastocytosis

Abstract: Systemic mastocytosis (SM) is a highly heterogeneous disease with indolent and aggressive forms, with the mechanisms leading to malignant transformation still remaining to be elucidated. Here, we investigated the presence and frequency of genetic variants in 34 SM patients with multilineal KIT D816V mutations. Initial screening was performed by targeted sequencing of 410 genes in DNA extracted from purified bone marrow cells and hair from 12 patients with nonadvanced SM and 8 patients with advanced SM, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 68 publications
7
63
0
8
Order By: Relevance
“… 10 , 11 Recent data, however, have highlighted that the molecular landscape of AdvSM is complex, with at least one somatic mutation in addition to KIT D816V (eg, in ASXL1 , CBL , JAK2 , RUNX1 , SRSF2 , or TET2 ) being present in more than 60% of patients with AdvSM. 12 , 13 In more recent studies, several groups examined the prognostic impact of these mutations. The presence and number of additional molecular mutations, notably in SRSF2 , ASXL , and/or RUNX1 (S/A/R), have a strong adverse influence on progression (leukemic transformation) to secondary MCL and/or secondary acute myeloid leukemia (AML), response to treatment, and OS.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Recent data, however, have highlighted that the molecular landscape of AdvSM is complex, with at least one somatic mutation in addition to KIT D816V (eg, in ASXL1 , CBL , JAK2 , RUNX1 , SRSF2 , or TET2 ) being present in more than 60% of patients with AdvSM. 12 , 13 In more recent studies, several groups examined the prognostic impact of these mutations. The presence and number of additional molecular mutations, notably in SRSF2 , ASXL , and/or RUNX1 (S/A/R), have a strong adverse influence on progression (leukemic transformation) to secondary MCL and/or secondary acute myeloid leukemia (AML), response to treatment, and OS.…”
Section: Introductionmentioning
confidence: 99%
“…Karyotype abnormalities were detected in 32% patients with SM-AHN but rarely in patients with ASM [14,15]. The abnormalities were most often found in patients with SM-AML [7].…”
Section: Fig 4 Monocytes and Eosinophils In The Bone Marrow [Mgg Stmentioning
confidence: 97%
“…By contrast, a few patients with AdvSM show a more favorable clinical behavior with prolonged survival rates. Recent investigations have suggested that the absence of mutations in genes other than KIT including SRSF2, ASXL1, RUNX1, and EZH2 might be associated with better prognosis in terms of OS in patients with AdvSM (Jawhar et al, 2016;Muñoz-González et al, 2018).…”
Section: Classification and Prognostic Stratification Of Mastocytosismentioning
confidence: 99%